The Influence of Flexible Employment on Workers’ Wellbeing: Evidence From Chinese General Social Survey - Liu, Teng; Liu, Qian; Jiang, Daokui (Frontiers in Psychology, 2022)
Based on the 2017 China General Social Survey (CGSS) data, with 5439 observations as research objects, this paper empirically tests the impact of flexible employment on workers’ well-being, and introduces labor income as mediator and social security as moderator to explore the mechanism of action. The empirical results show that: flexible employment has an inverted U-shaped relationship with workers’ well-being, which indicates that increasing employments’ flexibility will first rise and then reduce their perceived subjective well-being after reaching the peak; labor income plays a mediating role in the relationship of flexible employment and well-being of workers; social security moderates the mediating effect of labor income whereas the moderating role in the relationship between flexible employment and workers’ well-being is not observed. Implications and future development of flexible employment are discussed.